Three new species of Krogia (Ramalinaceae, lichenized Ascomycota) from the Paleotropics - Sonja Kistenich; Jouko K. Rikkinen; Holger Thüs; Charles Santhanaraju Vairappan; Patricia A. Wolseley; Einar Timdal (2018)
Krogia borneensis Kistenich & Timdal, K. isidiata Kistenich & Timdal and macrophylla K. Kistenich & Timdal are described as new species, the first from Borneo and the two latter from New Caledonia. The new species are supported by morphology, secondary chemistry and DNA sequence data. Krogia borneensis and K. isidiata contain sekikaic and homosekikaic acid, both compounds reported here for the first time from the genus. Krogia macrophylla contains an unknown compound apparently related to boninic acid as the major compound. DNA sequences (mtSSU and nrITS) are provided for the first time for Krogia and a phylogeny of the genus based on 15 accessions of five of the six accepted species is presented. Krogia antillarum is reported as new to Brazil, Guatemala and Mexico.